Är bor nödvändigt vid skogsgödsling i Sverige? - Sundberg, Mattias (2010)
This thesis has been made on behalf of SCA Skog AB to assess the need of boron in Swedish forest fertilization. Boron has been added to Swedish forest fertilizers since the beginning of the 1980s. This makes the fertilizers more expensive and therefore has the necessity of boron in Swedish forest fertilization been raised. The Swedish bedrock generally contains small amounts of boron. The boron in the bedrock is tightly bound to the mineral tourmaline and mostly unavailable for plants. This leads to that the contribution of boron to the soil from weathering is very low besides soils with marine sediments. Boron added to the soil originates by most parts from atmospheric deposition and weathering of organic matter. The deposition levels differ in different parts of Sweden. In northern Sweden the deposition levels are low except from a belt along the coastline. The levels in southern Sweden are considerably higher. Therefore most of the boron supply to the trees has to be covered by weathering of organic matter, especially in northern Sweden. The boron levels in the majority of the surveys found in literature have been lowered after fertilization. Despite the lower levels of boron, growth disturbance have in most cases only occurred to a limited extent. When growth disturbance have occurred the stand has been fertilized more than one time and with shorter interval than practiced in commercial forestry. The stands were with few exceptions located in the inland of northern Sweden. The amount of nitrogen applied to the stands exceeded in most cases the levels 150 kg/ha, which are normally applied in commercial forestry. The lack of growth disturbance indicates that the boron supplied by deposition and above all from weathering of organic matter was sufficient to cover the boron needs of the trees, even though the trees have been fertilized previously. Growth disturbance after a first fertilization are nonexistent in Sweden. If growth disturbance occur after the second or third fertilization, the economical effect ...